1997
DOI: 10.1210/jcem.82.10.4400
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution of Estrogen Receptors Alpha (ER-α) and Beta (ER-β) mRNA in the Midgestational Human Fetus

Abstract: We compared the expression profiles of the mRNAs of both estrogen receptors, ER-alpha and the recently cloned ER-beta, in the midgestational human fetus by semiquantitative RT-PCR. ER-alpha was most abundant in the uterus, and smaller quantities were detected in the ovary, testis, skin and gut. High amounts of ER-beta mRNA were present in fetal ovaries, testes, adrenals and spleen. In these tissues, the levels of ER-beta mRNA were higher than ER-alpha. In the uterus, however, ER-alpha mRNA was more abundant, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
2
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(54 citation statements)
references
References 0 publications
4
46
2
2
Order By: Relevance
“…In addition, ERβ was observed in the smooth muscle cells of the caput and corpus epididymis. Our results are consistent with the findings of studies performed on human testis (Brandenberger et al, 1997;Takeyama et al, 2001) and suggest that the effects of oestrogens, predominantly via ERβ, may play an important role in the development of the male reproductive organs, but not in the early stage. The presence of ERα in the efferent ducts in the porcine fetus corresponds with receptor localisation in newborn piglets (Nielsen et al, 2001), goat (Goyal et al, 1997) and rodents (Hess et al, 1997;Nielsen et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, ERβ was observed in the smooth muscle cells of the caput and corpus epididymis. Our results are consistent with the findings of studies performed on human testis (Brandenberger et al, 1997;Takeyama et al, 2001) and suggest that the effects of oestrogens, predominantly via ERβ, may play an important role in the development of the male reproductive organs, but not in the early stage. The presence of ERα in the efferent ducts in the porcine fetus corresponds with receptor localisation in newborn piglets (Nielsen et al, 2001), goat (Goyal et al, 1997) and rodents (Hess et al, 1997;Nielsen et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…50) On the other hand, Zhou et al 44) showed that E 2 treatment of MSC cells from OVXed and sham-operated mouse resulted in a decrease in ERb mRNA and protein expression which was accompanied by upregulation of osteogenic genes. In our present study we were unable to detect the ERb mRNA of the same basepair length reported in the literature, 33) either because they are expressed at a low level to be detectable or are not present in the SaOS-2 cell cultures. Therefore, the involvement of ERb in the E 2 action in our system can be excluded.…”
Section: )contrasting
confidence: 72%
“…The quantitative differences between cDNA samples were calculated after normalising in the corresponding GAPDH PCR product. The primers for ERa 32) and ERb 33) were chosen in the N-terminal A/B region, spanning one intron from published sequences as follows:…”
Section: Methodsmentioning
confidence: 99%
“…103 In humans, studies of ERs expression in the fetus, which is exposed to high estrogen levels, 104,105 from the 20th to the 38th gestational week, in the definitive zone of the adrenal cortex showed higher levels of ERβ than ERα mRNA. 104 The predominant ERβ expression was confirmed in…”
Section: Expression Of Ers In the Normal Adrenal Glandmentioning
confidence: 99%